2020
DOI: 10.1177/1071100720917375
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Spring Ligament Reconstructions Using Either Hamstring Allograft or Synthetic Ligament Augmentation

Abstract: Background: Idiopathic flatfeet are usually caused by attenuation of the medial soft tissues rather than a lateral osseous deficiency. Debate continues on whether spring ligament attenuation or posterior tibial tendon (PTT) dysfunction is the initial driver for the deformity. Our comparative prospective study aimed to quantify the radiological and clinical outcomes of 2 techniques for spring ligament reconstruction using a hamstring graft or a synthetic ligament. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…4 However, there have been few in vivo studies demonstrating the efficacy of SLR in PCFD, and those that do exist are limited by the small number of patients included in each study or their short-term follow-up. 6,20 We believe that the current study represents the largest cohort of SLR to date, as well as the longest follow-up of allograft reconstruction technique.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…4 However, there have been few in vivo studies demonstrating the efficacy of SLR in PCFD, and those that do exist are limited by the small number of patients included in each study or their short-term follow-up. 6,20 We believe that the current study represents the largest cohort of SLR to date, as well as the longest follow-up of allograft reconstruction technique.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, Heyes et al compared 17 SLRs utilizing synthetic ligament augmentation to 16 reconstructions using hamstring allograft, with a minimum of 1 year of follow-up. 20 In their study, synthetic ligament augmentation resulted in superior patient-reported outcomes compared to allograft reconstruction, and 2 patients in the allograft group required revision due to pain and deformity recurrence. However, their technique did not include the tibionavicular limb, unlike the technique described in this article.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…7,15,21,27 In the last decade, there has been an increasing appreciation on the importance of the ligamentous structures of the medial longitudinal arch. 17,29 A consensus paper was developed leading to renaming of the condition, but the importance of the distal aspect of the MLA was not discussed. 28 Nevertheless, studies on hallux valgus surgery have identified pes planus deformity as a major factor in recurrence of hallux valgus following reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Heyes et al 36 compared synthetic augmentation to semitendinosus allograft. Their synthetic technique involved proximal fixation to the sustentaculum tali but distal fixation to the medial cuneiform instead of the navicular to additionally reconstruct the naviculocuneiform ligament.…”
Section: Treatmentmentioning
confidence: 99%